Sensitivity analysis for joint optimization of reliability design and LOR considering CFR and TDFR approach. (2021) - Rawat, Manish; Choubey, Mayank
Abstract: This analysis is conducted to test sensitivity of the developed integrated model for reliability and maintenance decisions for fleet system. Sensitivity analysis is an important analysis to justify the model sensitivity considering the different model parameters. The parameters of integrated model are mean time in transportation delay, maintenance, and repair time at depot and at original equipment manufacturer. Sensitivity analysis of integrated model parameters is carried out to establish the minimum fleet maintenance life cycle cost. This analysis uses maintenance equipment cost, transportation cost and consumable cost. In this analysis, the different failure rates of the component approach are used i.e., Constant Failure Rate CFR and Time-dependent Failure Rate (TDFR). Therefore, to calculate the time to failure of the parts, Exponential distribution and Weibull distribution are used, respectively. The result shows that consumables cost, and transportation cost are sensitive for integrated model.